2017
DOI: 10.1186/s12984-017-0260-z
|View full text |Cite
|
Sign up to set email alerts
|

Inter-rater reliability of kinesthetic measurements with the KINARM robotic exoskeleton

Abstract: BackgroundKinesthesia (sense of limb movement) has been extremely difficult to measure objectively, especially in individuals who have survived a stroke. The development of valid and reliable measurements for proprioception is important to developing a better understanding of proprioceptive impairments after stroke and their impact on the ability to perform daily activities. We recently developed a robotic task to evaluate kinesthetic deficits after stroke and found that the majority (~60%) of stroke survivors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Studies evaluating other assessment approaches using various matching paradigms for different upper limb joints [ 14 , 31 , 32 , 34 , 35 , 38 , 41 , 50 , 54 , 56 , 60 ] or similar joint position DL estimation methods [ 34 , 59 ] reported coefficients of reliability ranging from fair to excellent for most outcome measures. However, it is difficult to compare results, as other approaches may measure different aspects of proprioception, or because some studies investigated the reliability in NIC subjects instead of in the target population, which may lead to non-representative results, due to different inter- and intra-subject variabilities [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies evaluating other assessment approaches using various matching paradigms for different upper limb joints [ 14 , 31 , 32 , 34 , 35 , 38 , 41 , 50 , 54 , 56 , 60 ] or similar joint position DL estimation methods [ 34 , 59 ] reported coefficients of reliability ranging from fair to excellent for most outcome measures. However, it is difficult to compare results, as other approaches may measure different aspects of proprioception, or because some studies investigated the reliability in NIC subjects instead of in the target population, which may lead to non-representative results, due to different inter- and intra-subject variabilities [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…To increase clinical acceptance, set-up and testing time, as well as the complexity and cost of the robotic devices should be reduced as much as possible. While some of these properties have been evaluated for matching and perturbation assessments, mostly targeting proximal joints such as shoulder and elbow (e.g., [ 38 , 54 , 60 ]), assessments estimating proprioceptive difference thresholds at finger joints have not been sufficiently optimized and evaluated so far.…”
Section: Introductionmentioning
confidence: 99%
“…The KINARM robot is a validated, well-studied, objective measure of sensorimotor function. Previous studies have demonstrated that the retest reliability of visually guided reaching [27, 48], kinesthesia [54], and position matching [28, 48] tasks is strong. The retest reliability of the object hit may be more variable, as retest reliability is high in adults [46], but a learning effect is seen in pediatric population [48].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, robotic devices, because of their built-in technology in terms of sensors and actuators, are able to objectively quantify the motor status of patients after brain damage, as well as their motor recovery. In fact, such devices are able to acquire kinematic and kinetic data which are processed to obtain quantitative indices [23][24][25][26][27][28][29][30][31][32][33][34]. These robot-derived measures can potentially add meaningful information about the patient's performance, helping the clinicians in patient's assessment.…”
Section: Introductionmentioning
confidence: 99%